G224 Development of cardiovascular risk factors in children with type 1 diabetes – a longitudinal cohort study. (12th March 2018) - Jones, S; Kanolkar, A; Matyka, K; Gevers, E; Allgrove, J; Stephenson, T; Amin, R
Abstract : Aims: Cardiovascular disease is the leading cause of death in adult diabetes. Atherosclerosis is related to modifiable risk factors beginning in childhood but can be reversed. Screening for complications is recommended from 12 years in the UK. This study investigated the prevalence and evolvement from diagnosis of cardiovascular risk factors (hypertension, obesity (BMI), dyslipidaemia, albuminuria) in an ethnically diverse population of children with Type 1 diabetes (T1D). Methods: The study included all children diagnosed with T1D attending three paediatric diabetes clinics in East London between 2005–2015. Clinical and demographic information was collected prospectively during routine check-ups. Linear longitudinal mixed effects modelling (growth curve analyses) were used to analyse the development of cardiovascular risk factors from diagnosis. Models were adjusted for age, gender, ethnicity, diabetes clinic, glycated haemoglobin (HbA1c ). Results: Of 565 children 60% were non-white, of whom 8% were Bangladeshi and 8% from Somali backgrounds. Mean age at diagnosis was 8.5 years (0.9–19.4). Mean length of follow-up was 4.3 years (0–10.8). There was variation between clinics in commencing screening, range 8.8–13.8 years (p<0.001). 33% of all measures demonstrated an unhealthy BMI, 15% revealed microalbuminuria, 66% were above lipid targets with 5% reaching treatment thresholds. The frequency of abnormalities before or after 12 years of age was unchanged. Longitudinal modelling revealed mean increases in BMI (0.6 kg/m 2, 95% CI: 0.6 to 0.7), blood pressure (1.8 mmHg, 1.5–2.1), total cholesterol (0.05 mmol/mol, 0.03–0.06) and low density lipoprotein (LDL) (0.2 mmol/mol, 0.01–0.04) per year from diagnosis for the entire cohort. HbA1c directly affected all variables other than albuminuria. Results from subgroup analysis in children over 12 years old were similar but not statistically significant. There was significant ethnic variation: Annual increments were greater for Bangladeshi children's cholesterol and LDL (0.38 mmol/mol, 0.1–0.6 and 0.32 mmol/mol, 0.09–0.55 respectively) and Somali children's BMI (1.6 kg/m 2, 0.7–2.5) compared to White. Conclusions: Levels of abnormalities were above regional and national averages in children of all ages. Somali and Bangladeshi children had less favourable profiles, which supports findings of increased cardiovascular risk in these ethnicities. Commencing screening in younger children and introducing tailored interventions for ethnic minorities with T1D may help reduce cardiovascular events in adulthood.